2022
DOI: 10.3390/pharmaceutics14040807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Optimization of Prolonged Release Mucoadhesive Tablets of Dexamethasone for Wound Healing: In Vitro–In Vivo Profiling in Healthy Volunteers

Abstract: The aim of the projected study was to design and develop a novel strategy for evaluating the mucoadhesive potential of polymeric tablets of dexamethasone (DXM) for local delivery against wounds. Therefore, formulations (Q1–Q7) were synthesized via direct compression method by varying the concentrations of polymers, i.e., ethyl cellulose (EC) and agar extract (AG). Moreover, the mucoadhesive polymeric tablets were characterized via physicochemical, in vitro, ex vivo and in vivo experiments. However, physicochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…These dressings were effective in preventing wound fibrosis. In another study, it was shown that a much lower concentration (0.5–3.5 μg/mL), obtained with Dex-P releasing from cellulose/agar tablets, is effective to trigger buccal wound healing . The concentrations of Dex-P in aerogels and cryogels obtained in our work (some tens of μg/mL, see Figure S3) are in between the values presented in the publications cited above; by modulating the type of material (cryogel or aerogel), its density, and the drug concentration in the loading bath, drug concentration in our porous chitosans can be adjusted to the desired therapeutic response.…”
Section: Resultssupporting
confidence: 69%
“…These dressings were effective in preventing wound fibrosis. In another study, it was shown that a much lower concentration (0.5–3.5 μg/mL), obtained with Dex-P releasing from cellulose/agar tablets, is effective to trigger buccal wound healing . The concentrations of Dex-P in aerogels and cryogels obtained in our work (some tens of μg/mL, see Figure S3) are in between the values presented in the publications cited above; by modulating the type of material (cryogel or aerogel), its density, and the drug concentration in the loading bath, drug concentration in our porous chitosans can be adjusted to the desired therapeutic response.…”
Section: Resultssupporting
confidence: 69%
“…However, the cell viability for all the formulations with a modified polymeric system was also higher than 70% as compared to the control, i.e., 45%, with a statistical significance of (p < 0.05), as shown in Figure 8. The peaks of MET and SIT were separated according to the devised conditions with the respective values of 1.96 and 3.70 min, as reported in the preliminary findings associated with the current study [41].…”
Section: In Vitro Cytotoxicity Analysismentioning
confidence: 81%
“…Surface pH For the measurement of surface pH, the tablets were allowed to swell in 10 mL of distilled water adjusted to pH 6.8 for 2 h, at 37.5 • C on a hot plate. The surface pH was then measured by touching the electrode of the pH meter on the surface of the tablet and allowing it to equilibrate approximately for 1 min [26,41].…”
Section: Physical Characterization Of the Formualted Tabletsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the mechanism of release, it is worth looking at the diffusional exponent n for Korsmeyer-Peppas kinetics, which describes the release as anomalous (for values 0.43 < n < 0.89), suggesting that the combination of diffusion and erosion contributes to the control of drug release [26]. This release mechanism is characteristic of many PVP-based mucoadhesive formulations [27,28]. To better illustrate the differences in the release profiles, in the absence of statistically significant differences between the profiles for different compression forces, the profiles for TP and TN were averaged, and are presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%